Estudio de tres métodos de control de candidatus liberibacter solanacearum en seis ecotipos de Tomate de árbol solanum betaceum en etapa de desarrollo, Salache -Cotopaxi 2021. - Jácome Quiroz, Luis Fernando (2022)
This research was carried out at the Salache campus of the Technical University of Cotopaxi in the Eloy Alfaro parish, Latacunga canton, at an altitude of 2,710 m.a.s.l., to detect the best preventive method, considering PCR results acquired from a molecular biology laboratory, then ecotype capable of presenting resistance and tolerance to the permanent disease of tomato was identified through a multivariate analysis of principal components and clusters, in which a minimum population of the vector Bactericera cockerelli was evidenced, obtained from weekly monitoring, which influenced the rotation of active ingredients, generating a qualified environmental impact through the Leopold Matrix. Negative PCR results were obtained in the three control methods implemented with gentamicin sulphate and oxytetracycline hydrochloride from nursery and in the field (C), only in the field (A1) and without chemicals against bacterium (A0), in which three ecotypes from Granel, Atuntaqui and La Providencia resisted the disease in the sector, controlling the vector at the development stage with the molecules: imidacloprid, asoxystrobin, tridemorph, abamectin, pyridaben, formetanate, fipronil, profenofos and thiamethoxan, causing an unfavourable environmental impact during the development stage of the tree tomato. In order to reduce the detrimental effect of the vascular pathogen, the tolerant ecotypes detected in the research should be implemented, including a random placement of adherent traps to create greater control over the vector, preventing the transmission of Candidatus Liberibacter solanacearum to the crop.